The Dominant Factor Causing Low Adherence of Pregnant Women Consuming Zinc Tablets in the Work Area of the Public Health Center Stem Quiz Deli Serdang Regency Year 2022 - Suhartini, Suhartini; Sunartono, Sunartono; Pasaribu, Masdalifa (Jurnal EduHealth, 2023)
Background: The zinc supplementation program is an effort that has been made by the Indonesian government to prevent anemia in pregnancy which is given in pill form but the incidence of anemia and pregnancy complications is still high due to low adherence of pregnant women in consuming iron tablets.The purpose of this study was to determine the dominant factors causing low adherence of pregnant women to consuming zinc tablets in Batang Kuis Health Center work area in 2022. Research Methods: The research design uses a descriptive analytic method with a cross sectional research design. The study population was all pregnant women who came for a visits at Batang Kuis health center and classes for pregnant women carried out at the Pustu and Poskesdes in the working area of Batang Kuis health center. The number of samples involved 124 people using accidental sampling. Univariate data analysis using frequency distribution tables, bivariate analysis using Chi-Square, multivariate analysis using multiple logistic regression tests. Results: The significant predisposing factors were the knowledge variables p - value (0.000) and parity p - value (0.042), which were not significant for the educational variables p - value (0.193) and employment p - value (0.140). The significant enabling factors were place of residence variable p - value (0.001), socioeconomic p - value (0.003), quantity of visits anc p - value (0.007), quality anc p - value (0.011). The significant reinforcing factors were the variables of the role of health workers p - value (0.022) and motivation p - value (0.000), not significant to the family/community support variable p - value (0.227). multivariate analysis showed that the dominant factor was knowledge with p-value (0.001) and OR 179.5. Conclusion: pregnant women with more or less dominant knowledge cause low adherence of pregnant women in consuming zinc tablets.